Development of a causal model of self-regulated learning by students at Loei Rajabhat University - Kumyoung, Anuphum; Kessung, Patthraporn; Pinasa, Chaimongkhon; Srijumnong, Jutamas; Inyai, Chao (Frontiers in Education, 2024)
Introduction Self-regulated learning is an active process in which learners employ self-directed behaviors, thoughts, and actions to attain learning objectives. It is essential for students as it can result in improved academic achievement, task completion, and the acquisition of life skills. The objectives of this research were to examine the congruence between a causal model of self-regulated learning and empirical data and to investigate the direct and indirect effects of the model on a sample of 660 students from Loei Rajabhat University. Methods The data were analyzed using structural equation modeling. The results indicate that the causal model of self-regulated learning aligns with the empirical data. Results The study showed that self-efficacy, achievement motive, and learning by imitation variables had a favorable impact on self-regulated learning. The achievement motive and learning by imitation have indirect impacts on self-regulated learning through the self-efficacy variable. The findings suggest an increase in self-efficacy, achievement motive, and learning by imitation. Increasing self-efficacy, achievement motive, and learning by imitation among students may be an effective strategy for enhancing the efficiency of self-regulated learning. Discussion This research suggests that teachers should organize teaching and learning activities that promote achievement motivation and develop self-efficacy, and they should be good role models for students. All parties, including administrators, should implement policies that promote and develop activities to create incentives for achievement. Self-efficacy and learning by imitation are necessary for students to practice self-regulated learning in the future.